Serum phosphatidylinositol as a biomarker for bipolar disorder liability. (23rd February 2017) - Knowles, Emma EM; Meikle, Peter J; Huynh, Kevin; Göring, Harald HH; Olvera, Rene L; Mathias, Samuel R; Duggirala, Ravi; Almasy, Laura; Blangero, John; Curran, Joanne E; Glahn, David C
Abstract: Objectives: Individuals with bipolar disorder (BPD) exhibit alterations in their phospholipid levels. It is unclear whether these alterations are a secondary consequence of illness state, or if phospholipids and illness risk overlap genetically. If the latter were true, then phospholipids might provide key insights into the pathophysiology of the illness. Therefore, we rank‐ordered phospholipid classes by their genetic overlap with BPD risk in order to establish which class might be most informative in terms of increasing our understanding of illness pathophysiology. Methods: Analyses were conducted in a sample of 558 individuals, unselected for BPD, from 38 extended pedigrees (average family size=14.79, range=2−82). We calculated a coefficient of relatedness for all family members of nine individuals with BPD in the sample (N=185); this coefficient was set to be zero in unrelated individuals (N=373). Then, under an endophenotype ranking value (ERV) approach, this scalar index was tested against 13 serum‐based phospholipid concentrations in order to rank‐order lipid classes by their respective overlap with BPD risk. Results: The phosphatidylinositol class was significantly heritable ( h 2 =0.26, P =6.71 × 10 −05 ). It was the top‐ranked class, and was significantly associated with BPD risk after correction for multiple testing (β=−1.18, P =2.10 × 10 −03, ERV=0.49). Conclusions: We identified a peripheral biomarker, serum‐based phosphatidylinositol, which exhibits a significant association with BPD risk. Therefore, given that phosphatidylinositol and BPD risk share partially common etiology, it seems that this lipid class warrants further investigation, not only in terms of treatment, but also as a promising diagnostic and risk marker.